Novel Design Method for the Roll Forming Process and Improved Forming Quality of 316L Stainless Steel BPP Flow Channels with Right-Angled Sidewalls - Fuqiang Zhao; Hugang Tian; Qingxue Huang; Yanlei Zhang; Xiaolong Xie; Zhigang Qi; Shuaifeng Chen (Chinese Journal of Mechanical Engineering)
Abstract The forming quality of metal bipolar plate (BPP) flow channels in proton exchange membrane fuel cells (PEMFCs) is a key factor affecting battery performance. A flow channel with straight sidewalls and a low thinning rate can enhance battery output. Roll forming, as a new technology for BPP production, offers advantages such as a low thinning rate and high efficiency. However, existing roll curve design methods struggle to accommodate both low thinning rates and straight sidewall angles simultaneously. This study aims to develop flow channels with right-angled sidewalls, which provide benefits such as a low thinning rate, reduced residual stress, and high accuracy. A roller tooth profile was designed to achieve a flow channel with right-angled sidewalls and minimal thinning. Simulations and experiments were conducted to validate the feasibility of this novel design method for the roll forming process. The study investigated the effects of roller tooth parameters on sidewall angle, thinning rate, and residual stress. A multifactor evaluation method was developed to optimize the tip fillet radius and the tooth profile backlash of the roller. The results indicated that the tip fillet radius and the tooth profile backlash were negatively correlated with the sidewall angle. As the tip fillet radius and tooth profile backlash increased, the thinning rate and residual stress decreased. With a tip fillet radius of 0.25 mm and a tooth profile backlash of 0.19 mm, the flow channel achieved an approximately right-angled sidewall, a maximum thinning rate of 7.7%, a 29.6% reduction in maximum residual stress, and maximum and average residual stress imbalance values of 7.1% and 3.2%, respectively. This study proposes a new design method for a right-angled sidewall runner roller gear profile, facilitating the roll forming of metal BPPs with right-angled sidewalls and minimal thinning. This method provides theoretical support for the large-scale application of roll forming in the manufacture of PEMFC BPPs.